Situational expectancies and task values: Associations with students' effort. (February 2017) - Dietrich, Julia; Viljaranta, Jaana; Moeller, Julia; Kracke, Bärbel
Abstract: According to expectancy-value theory, expectancies and task values are precursors for investing effort into learning. To date, it remains largely unknown (1) to what extent expectancies and values change from one learning situation to another and (2) to what extent inter-individual findings reflect intra-individual motivational processes. We applied an intensive longitudinal design in a sample of 155 pre-service teacher students attending a lecture. Across ten lessons with varying topics, students reported three times per lesson on their situational effort, expectancies, task values (intrinsic, attainment, utility), and cost. We used multilevel structural equation modeling with learning situations (L1), nested in topics (L2), and nested in students (L3). The results showed variability on all levels. We found positive associations of effort with task values on each level, positive associations with expectancies on the learning situation and topic levels, and smaller negative associations with cost on the topic level. Highlights: We broaden expectancy-value theory (EVT) research with situational measures. We measure situational fluctuations in expectancy and task value. We test whether expectancy and value predict effort on an intra-individual level. Findings show that expectancy and value vary across learning situations and topics. Predictions from EVT concerning effort apply to the level of situations and topics.